2005
DOI: 10.1083/jcb.200505061
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for Gab2 in bFGF-mediated cell survival during retinoic acid–induced neuronal differentiation

Abstract: Gab proteins amplify and integrate signals stimulated by many growth factors. In culture and animals, retinoic acid (RA) induces neuronal differentiation. We show that Gab2 expression is detected in neurons in three models of neuronal differentiation: embryonic carcinoma (EC) stem cells, embryonic stem cells, and primary neural stem cells (NSCs). RA treatment induces apoptosis, countered by basic FGF (bFGF). In EC cells, Gab2 silencing results in hypersensitivity to RA-induced apoptosis and abrogates the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
(60 reference statements)
1
42
0
Order By: Relevance
“…It has been shown that RA treatment induces apoptosis in embryonic carcinoma cells. bFGF was reported to suppress RA-associated apoptosis, possibly via the PI3K (phosphoinositide 3 kinase) pathway (Mao and Lee, 2005;Appel and Eisen, 2003). However, the interaction between bFGF and RA during neural differentiation is a challenging question and this interaction in AECs and RA-associated apoptosis at the used dose of RA remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that RA treatment induces apoptosis in embryonic carcinoma cells. bFGF was reported to suppress RA-associated apoptosis, possibly via the PI3K (phosphoinositide 3 kinase) pathway (Mao and Lee, 2005;Appel and Eisen, 2003). However, the interaction between bFGF and RA during neural differentiation is a challenging question and this interaction in AECs and RA-associated apoptosis at the used dose of RA remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF is highly expressed in the nervous system and is required for normal cortex development (Dono et al, 1998). It has been shown that (Mao and Lee, 2005). Other factors are also used for neural differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…WT, 3YF, and DM Gab2 cDNAs (20) were cloned into pMSCV-IRES-EGFP (42). Short hairpin RNAs (shRNAs) targeting the 3Ј untranscribed region (UTR) of murine Gab2 and Gab3 cloned into pU6 or pLentiLoX have been described (36). dsRed was substituted for green fluorescent protein (GFP) in pLentiLoX to create pLentiLoX-dsRed.…”
Section: Using Bm Cells From Gab2mentioning
confidence: 99%
“…MISSION lentiviral shRNAs targeting murine JNK1 were cloned into pLKO.1 (shJNK1-1, TRCN0000012583; shJNK1-2, TRCN0000012585; shJNK1-3, TRCN0000012584; shJNK1-4, TRCN0000012586 [Sigma-Aldrich]). Ecotropic retroviruses and vesicular stomatitis virus G (VSVG)-pseudotyped lentiviruses were produced in 293T cells (36). 32D.R cells were electroporated with pU6-shGab2 and pPUR (Clonetech) or transduced with GFP-shGab2 or dsRed-shGab3 lentiviruses separately or together and flow sorted based on GFP or dsRed expression.…”
Section: Using Bm Cells From Gab2mentioning
confidence: 99%
“…However, the critical Shp-2 substrate in controlling Ras/Erk activation is still not clear. Gab2 association with p85 is critical for cytokine, Fc-receptor, and growth factor-evoked PI3K activation (19,29).…”
mentioning
confidence: 99%